4CPS-269 Are patients and healthcare professionals willing to exchange the price of treatments to choose a biosimilar? experience based on the delphi method. (March 2019) - Gary, C; Schiavon De Jodar, A; Deljehier, T; Xuereb, F; Bouabdallah, K; Pigneux, A; Milpied, N; Breilh, D
Abstract : Background: Health policies require improving the efficiency of healthcare by supporting the development of biosimilar drugs. French policies request that appropriate information should be given to patients who receive a biosimilar. According to an international study, only 6% of the general population is aware of what is a biosimilar. This data suggests that appropriate information about biosimilar is complicated and time-consuming. Few data are published on patients' opinions concerning cost and biosimilar drugs. Purpose: We aimed to establish a consensus on the important information that should be given to patients during an initial consultation, and to define to what extent we can discuss cost and biosimilar choice. Material and methods: This study was conducted in the department of haematology, a panel of 72 'experts' consisting of 50 patients and 22 healthcare professionals (HCP). The DELPHI method allowed the collection of the experts' opinions in a prospective way. We defined 12 items to be assessed in two rounds: one, choosing information useful to know; and two, prioritising essential information. In the third round, after correct explanations about biosimilars, experts were given a choice: accept or reject the biosimilar drug with detailed arguments. Results: First, experts assessed: 'cost of treatment', 'biosimilar/generic drug' useful to know up to 45% (patients: 63%, HCP: 38%) and 43% (patients: 57%, HCP: 38%), respectively. The following items: 'side effects (SE)' and 'food/drug prohibited' were selected as useful to know by 100% of the experts. Then, 'correct conduct in case of SE', 'SE' and 'intake modalities' were considered essential by the experts. Unexpectedly, 'cost' was mentioned by only 7% of the patients. At the third round, 55% of the patients accepted the biosimilar, 40% did not decide and trusted in their HCP's decision and one patient rejected a biosimilar even when not convinced by HCP. Among HCP, 93% accepted a biosimilar and only one HCP refused it. The main argument for choosing a biosimilar drug was 'economic reason'. Conclusion: These results suggest that patients and HCP are aware of the increasing cost of the drugs and the economic impact on society. Most patients trust their HCP in the choice of the most efficient therapy. Further investigations are needed to confirm these results, with a larger cohort of patients. References and/or acknowledgements: No conflict of interest.